Mortality and recurrence of vascular disease among stroke patients treated with combined TCM therapy - 赵晓峰 苏世君 国云红 王舒 (Journal of traditional Chinese medicine, 2012)
OBJECTIVE：To confirm the long-term outcomes of stroke patients and determine predicting factors for death,recurrence of vascular events and poor outcome（either recurrence or death） after the use of combined TCM therapy.METHODS：This was a retrospective hospital-based cohort study and was performed in the First Affiliated Hospital of Tianjin University of Traditional Chinese Medicine in Tianjin.All subjects with stroke consecutively admitted to an inpatient ward of the Acupuncture Department from January 1,2008,to December 31,2008 were retrospectively followed through one year.The main outcomes were either a recurrence of vascular events,,mortality or both.Risk factors were recorded from medical records.Multivariate regression models were used to analyze predictors.The following independent variables were used：age,gender,hypertension,ischemic heart disease,atrial fibrillation,diabetes mellitus,carotid arterial lesions and history of stroke.RESULTS：Four-hundred and five patients were included.The 1-year mortality rate was 11.11%.23.70% of the patients had a recurrent vascular event,and 30.86% suffered a poor outcome.Multiple logistic regression analysis found that previous stroke,and advanced age were predictors of death within one year,Recurrence of vascular events was associated with carotid arterial lesions,history of diabetes and previous stroke.Long-term poor outcome was predicted by advanced age,history of diabetes,and previous stroke.CONCLUSION：Age,previous stroke,carotid arterial lesions and diabetes history seem to have different impacts on the three outcomes within one year.Our findings provide important data for planning future hospital register studies of stroke patients in TCM hospitals.